Paradoxical Reaction to Golimumab: Tumor Necrosis Factor α Inhibitor Inducing Psoriasis Pustulosa - Marien Siqueira Soto Lopes; Beatriz Moritz Trope; Maria Paula Rua Rochedo Rodriguez; Rachel Lima Grynszpan; Tullia Cuzzi; Marcia Ramos- (Karger Publishers, 2013)
Importance: Golimumab is a human monoclonal antibody, used for rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis. Adverse reactions are increasing with this class of medication (tumor necrosis factor α inhibitors). Observations: The authors present a case of a female patient who presented with psoriasis pustulosa after the use of golimumab for rheumatoid arthritis. Conclusions and Relevance: Paradoxically, in this case, golimumab, which is used for psoriasis, induced the pustular form of this disease. We are observing an increasing number of patients who develop collateral effects with tumor necrosis factor α inhibitors, and the understanding of the mechanism of action and how these adverse reactions occur may contribute to avoid these sometimes severe situations.